Enhancing Student’s Public Speaking Skills: Evaluating the PIPA Model for Effective Communicative Speech - Pipit Rahayu; Eripuddin Eripuddin; Nia Ramadani (STAI Hubbulwathan Duri, 2024)
Assessing public speaking abilities is crucial in contexts such as the Puteri Indonesia Contest, where effective communication is key. This study used a descriptive qualitative approach, data was collected from video documentation. The population of the research is 20 students. The sample of the research is 10 students who take the data from 10 contestants from Puteri’s Indonesia Speech. The data were analyzed and obtained from 3 raters through the PIPA Persuasive Informative Presentation Assessment) Model. It consisted of organization, supporting materials, content, articulation, nonverbal communication, and visual aid. The result shows that one speech of the contestants was categorized in Advanced level in in nonverbal communication and articulation. Then, supporting materials, and content reached a proficient level. Lastly, there was no visual aids available during the grand final speech competition, they only got a minimal level of visual aids. Thus, visual aid is the weaknesses of PIPA model in the speech of the contestants. It was suggested to investigate for the next research.